Phase-sensitive evidence for pair density waves in a kagome superconductor - Xiao-Yu Yan; Guowei Liu; Hanbin Deng; Xitong Xu; Haiyang Ma; Hailang Qin; Junyi Zhang; Yuanyuan Zhao; Xiuhao Fan; Wei Song; Muwei Gao; Haitian Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
Pair density wave (PDW) exhibits periodic amplitude and sign modulations of the superconducting order parameter. Such a pairing state has long been proposed to be highly sensitive to nonmagnetic scattering, but its experimental realization remains elusive. Here, we find a nonmagnetic PDW-breaking effect in a kagome superconductor, using designer atomic nonmagnetic impurities and high-precision scanning tunneling microscopy (STM) at a base temperature of 30 mK. We detect 2 × 2 pair density modulations by Josephson STM with a superconducting tip and 2 × 2 pairing gap modulations by normal STM. We find that the pairing modulations in both cases are substantially suppressed upon doping the kagome lattice with dilute isovalent nonmagnetic impurities, whereas the charge order and uniform superconductivity remain robust. We further identify the correlation between atomic dopants and the local suppression of PDW. We attribute these findings to a nonmagnetic pair-breaking effect, arising from the phase modulation of PDW in the kagome d -orbital. Taken together with its signatures in other state-of-the-art spectroscopy and transport measurements linked by theory, our findings support the ground state of the kagome superconductor as a correlated topological phase with superconducting loop currents.